PENGEMBANGAN INSTRUMEN PENILAIAN KEMAMPUAN BERPIKIR TINGKAT TINGGI TENTANG MATERI SISTEM GERAK PADA MANUSIA UNTUK PESERTA DIDIK KELAS XI SMA/MA - Siregar, Zahra Salsabila; Ristiono, Ristiono; Alberida, Heffi (BIOCHEPHY: Journal of Science Education, 2023)
This research is a development research which aims to produce an assessment instrument with proper higher-order thinking skills on the subject of human movement systems. Assessment instruments are one example of teaching materials that can assist in the learning process. This research was conducted with a literature review on articles related to the 2017-2022 timeframe. It can be concluded that the development of higher order thinking skills instruments is feasible to be used as teaching materials that assist in the learning process.